The Relationship Between the Harmonious Passion Development and the Human Integral Development: Educational Perspective in Brief - Maria Szymańska (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: The scientific aim of the article is to learn the relationship between the integral human development and the development of harmonious passion (HP) and the human integral development and upbringing. THE RESEARCH PROBLEM AND METHODS: The research problem of the conducted research is contained in the question: What is the relationship between harmonious passion with the integral development of the educational entity. Answering this question enables the use of the hermeneutic method exploring the meaning of this phenomenological relationship. THE PROCESS OF ARGUMENTATION: The research process is epistemological in nature. It refers to the dualistic model of passion, particularly to the harmonious passion, and the integral human development. Noticing the correlation between the above-mentioned aspects can be a significant challenge for the teachers and students with their passionate attitude, discovering and forming their own identity. RESEARCH RESULTS: The analysis of the collected material indicated the importance of the development of a harmonious passion for the integral development of educational entities in the space of biological, psychological, social, cultural and spiritual life, and the formation of an autonomous identity. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: Theoretical research in the abovementioned area can draw the educators' attention to the harmonious passion seen in a multidimensional perspective, reflected in the educational activity, what needs revising and updating educational programs that stimulate the actualization of creative potential of educational entities. This can be used to get to know oneself, others and the world more deeply on the path of autonomous self-becoming.